Mengukur Tingkat Efisiensi Bank Pembiayaan Rakyat Syari’ah dengan Menggunakan Data Envelopment Analysis (DEA) - Arif Ramadhan; Didit Purnomo; Muhammad Muhtarom; Chuzaimah Chuzaimah (Cakrawala: Jurnal Studi Islam, 2017)
The purpose of this study is to analyze the efficiency level of Shari'ah People's Financing Bank (BPRS) in Surakarta City. The data used in this study is secondary data taken from www.ojk.co.id published by each Sharia Bank Financing (BPRS). This research uses input-output variable with Data Evelopment Analysis (DEA) method. The result of the research shows that in Quarter I - Quarter IV there is only one Sharia Bank Financing (BPRS) that experienced inefficiency. Based on the calculation using Data Evelopment Analysis (DEA), in Quarter II - Quarter IV BPRS Central Syari'ah Utama experienced inefficiency, whereas in Quarter I - IV IV BPRS Dana Amanah, BPRS Dana Mulia, BPRS Harta Insan Karimah showed efficiency. The period 2016 Quarter I - fourth quarter IV of Syari'ah People Financing Bank (BPRS) that is BPRS Dana Amanah, BPRS Dana Mulia, BPRS Harta Insan Karimah already 1,000 or experienced efficiency continue to take care during that quarter